MiR-618 suppresses the proliferation, invasion, and migration of non-small lung cancer via the JAK2/STAT3 axis - Ziyuan Chen; Wei Chen; Zhiqi Hong; Xianqiao Wu; Tianzheng Fang; Yufei Sheng; Shuai Fang; Chengwei Zhou (Journal of Cardiothoracic Surgery)
Abstract Objective The regulatory role of the miR-618/JAK2/STAT3 axis in non-small cell lung cancer cells (NSCLC) was investigated with the objective of identifying a target for the precise treatment of patients with NSCLC. Methods Initially, differential gene expression was identified in the GEO database, followed by a comprehensive bioinformatics analysis. The tissue and cell levels of miR-618 were assessed using qRT-PCR, while the protein levels of JAK2 and STAT3 were determined through western blotting analysis. The association between miR-618 and JAK2 was scrutinized through bioinformatics analysis and dual-luciferase experiments. To evaluate cell proliferation, migration, and invasion, MTT, wound-healing, and Transwell assays were employed. Results The expression of miR-618 is decreased in NSCLC, and it targets the JAK2/STAT3 pathway to inhibit the proliferation, invasion, and migration of NSCLC. Conclusion Our study demonstrates that a novel miR-618/JAK2/STAT3 signaling axis is involved in suppressing malignancy in NSCLC and provides a promising target for NSCLC therapy.